Certified quality systems and farming practices in olive growing: The case of integrated production in Andalusia. Issue 4 (December 2014) - Hinojosa-Rodríguez, Ascensión; Parra-López, Carlos; Carmona-Torres, Carmen; Sayadi, Samir; Gallardo-Cobos, Rosa
Abstract The competitiveness of the olive agrofood sector depends heavily on its ability to adapt to the current scenario of increasingly internationalized interchanges, segmentation of markets, differentiation of consumption behaviors, and changing public support for agriculture. Quality differentiation and certification through a Certified Quality System (CQS) ensure the quality of products and services beyond mandatory levels and generate a competitive advantage for certified firms. In the Andalusian olive-growing sector, the largest in the world, integrated production (IP) plays an important role. IP certifies a higher quality of the product and production process by guaranteeing the implementation of farming practices that are hypothetically more sustainable, environmentally friendly, profitable, fair for farmers, and healthy for consumers. This paper investigates the underlying factors that have conditioned the diffusion of IP and tries to confirm the differential and higher quality provided by this CQS. A survey of 400 farmers from the main olive-growing provinces of Andalusia was carried out in 2010/2011 on the basis of face-to-face interviews following a structured questionnaire. The results corroborate low levels of knowledge and adoption of most of the available CQSs in the sector. They also confirm the higher quality of IP olive products and processes since farmers adopting this CQS are implementing better farming practices from an agronomic, environmental and economic point of view. The better practices are especially those related to soil management, irrigation, phytosanitation and harvesting. Otherwise, olive farmers in general seem to be entrenched in a relatively closed information system where 'contagion' of information among themselves and from close sources is the main diffusion driver, with no significant influence from external sources such as public and private R&D institutions. Moreover, a lack of orientation of farmers toward satisfying customers' requirements when innovating was detected. Strengthening the diffusion of IP would require bringing information closer to farmers in an accessible manner. The work of R&D institutions is essential in this context. Special emphasis should be placed on the medium- to long-term economic benefits and improved competitiveness associated with IP, these being the main concerns of farmers. Improved access to credit would also probably encourage its adoption. It is also necessary to convince farmers of the environmental and social benefits associated with IP. Reinforcing public policies promoting the professionalization of the sector and training in marketing are also necessary measures.